THE CHALLENGES OF DIGITAL SUPPLY CHAIN IMPLEMENTATION: A CASE STUDY IN PROJECT MANTRA TOOL IN PT. UNIKACA PROBANA (UP) - Lim, Widyana; Firman, Aries (AIBPM Publisher, 2020)
PT. UNIKACA PROBANA (a disguised name) developed an auto-tracker for project management called MANTRA, as pioneer in digital supply chain transformation journey. MANTRA is a digitized innovation planning tool to automate master data management and packaging material development in single touch point. MANTRA is expected to help business by providing analytics and insights for better decision making. MANTRAâ€™s utilization rate is still not optimized yet â€“ 63% up to October 2019. This becomes the biggest challenge to be unlocked. Research goal is to help finding root causes and suggested actions for this tool to become more beneficial to users. This research uses qualitative methodology, with data and information collected using direct observation and interviewing nine respondents from three different clusters. Interview result are reflected through mind-mapping and narrowed into two factors: core technical capabilities and non-technical aspects. Several actions for utilization rate improvement are by introducing change-agent, distributing performance report, and transforming MANTRA from a â€œbychoiceâ€ to â€œmust-useâ€ tool. Final section concludes a diagnostic framework that can be utilized to implement digitization in supply chain environment.Keywords:Â digital supply chain, challenge, utilization rate, improvement, framework